2012
DOI: 10.1186/1471-2407-12-579
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessel hyperpermeability and pathophysiology in human tumour xenograft models of breast cancer: a comparison of ectopic and orthotopic tumours

Abstract: BackgroundHuman tumour xenografts in immune compromised mice are widely used as cancer models because they are easy to reproduce and simple to use in a variety of pre-clinical assessments. Developments in nanomedicine have led to the use of tumour xenografts in testing nanoscale delivery devices, such as nanoparticles and polymer-drug conjugates, for targeting and efficacy via the enhanced permeability and retention (EPR) effect. For these results to be meaningful, the hyperpermeable vasculature and reduced ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Tumor vascular permeability as well as the lack of functional lymphatic vessels influences angiogenesis, tumor growth and metastasis, and drug delivery [40–42]. Studies from Ho et al demonstrated that tumors grown orthotopically in the mammary fad pad exhibit a higher vascular size and density and thinner basement membranes compared to subcutaneously injected ones [17]. Similarly, prostate tumors have increased vascular density, vessel permeability, oxygenation, and VEGF expression when grown orthotopically as compared to in the subcutis [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor vascular permeability as well as the lack of functional lymphatic vessels influences angiogenesis, tumor growth and metastasis, and drug delivery [40–42]. Studies from Ho et al demonstrated that tumors grown orthotopically in the mammary fad pad exhibit a higher vascular size and density and thinner basement membranes compared to subcutaneously injected ones [17]. Similarly, prostate tumors have increased vascular density, vessel permeability, oxygenation, and VEGF expression when grown orthotopically as compared to in the subcutis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in vascular transport have been observed when comparing different tumor models, grown either orthotopically or ectopically. However there remains significant controversy on this topic, and while some studies have observed reduced transvascular transport of large macromolecules when tumors are grown orthotopically in the cranial microenvironment compared to their ectopic subcutis-implanted counterparts [15], higher vascular permeability and higher accumulation of nanocarriers has been observed when tumors were grown orthotopically in the liver and breast compared to their ectopic subcutaneous counterparts [16, 17]. Other discrepancies, such as growth rate, metastatic potential, and efficacy of treatment, have also been demonstrated across different tumor models.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ho et al . showed higher vascular density in orthotopic breast tumors compared to subcutaneous tumors of similar size [28], but the CD31 endothelial marker was utilized in their study, which makes it difficult to ascertain whether there was a similar difference in functional vasculature. Our study utilizes the perfusion marker DiOC7 in addition to CD31 to evaluate changes in the functional blood vessels, and highlights the importance of quantifying both total and functional vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Although antitumor activity against subcutaneous tumors is simple to evaluate by measuring the volume changes of tumors on the subcutis, subcutaneous and orthotopic tumors exhibit different pharmaceutical response . In addition, recent studies have revealed that ectopic and orthotopic tumors possess considerably different characters (e.g., tumor microenvironment and gene expression) . In particular, tumor microenvironments strongly affect tumor generation and drug responses .…”
Section: Introductionmentioning
confidence: 99%